Long-term survival after surgical management of neuroendocrine hepatic metastases - Glazer, Evan (2010)
Background:  Surgical cytoreduction and endocrine blockade are important options for care for neuroendocrine liver metastases. We investigated the long-term survival of patients surgically treated for hepatic neuroendocrine metastases. Methods:  Patients (n= 172) undergoing operations for neuroendocrine liver metastases from any primary were identified from a prospective liver database. Recorded data and medical record review were used to analyse the type of procedure, length of hospital stay, peri-operative morbidity, tumour recurrence, progression,and survival. Results:  The median age was 56.8 years (range 11.5–80.7 years). 48.3% of patients were female. Median overall survival was 9.6 years (range 89 days to 22 years). On multivariate analysis, lung/thymic primaries were associated with worse survival [hazard ratio (HR): 15.6, confidence interval (CI): 4.3–56.8, P= 0.002]. Severe post-operative complications were also associated with worse long-term survival (P < 0.001). A positive resection margin status (R1) was not associated with a worse overall survival probability (P∼ 0.8). Discussion:  Early and aggressive surgical management of hepatic metastases from neuroendocrine tumours is associated with significant long-term survival rates. Radiofrequency ablation is a reasonable option if a lesion is unresectable. R1 resections, unlike many other cancers, are not associated with a worse overall survival.